(untitled) (Lapai Journal of Economics, 2020)
This study shows the efficacy of the various non-pharmaceutical control measures in line with the international protocol against COVID-19 in Nigeria as well as offers a year’s projection of the likely effects of the disease in Nigeria. The study adopts a cutting edge variant of the SEIR epidemiological model and made use of a mathematical software Geogebrato estimate the model. The findings of the study indicates that the virus is not much a problem in Nigeria as it does not have the capacity of causing more death than usual and the adoption of more non-pharmaceutical control measures in the country for a year will not significantly improve the welfare of Nigerians.